Techno-Economic Analysis of Reverse Osmosis Desalination Plant Powered by Hybridized PV and CSP Systems for Irrigation Water - Eylül Gedik; Diego-César Alarcón-Padilla; Derek Baker (SolarPACES Conference Proceedings, 2023)
Large market opportunities exist for solar powered Reverse Osmosis (RO) desalination technologies in fertile but arid areas with large solar and sea water resources. A challenge to realizing these markets is the variable nature of solar resources, which for the desalination plant can lead to high water costs due to low capacity factors (CF) and increased maintenance costs due to repeated start-ups and shut-downs. A potential solution is to power RO plants using both PV and CSP with Thermal Energy Storage (TES) with an aim to reduce shut-downs, and increase CF. In this study, three solar energy systems to power RO are considered: 1) PV only; 2) CSP with central receiver (CR) and TES; 3) PV and CSP with CR and TES. Two RO operational strategies are considered: 1) nominal load only; 2) variable load between minimal and nominal. The performance of these systems is simulated for Mersin, Turkey, using TMY data. The PV and CSP with TES system and variable RO operation achieved the levelized cost of water (LCOW) 1.92 USD m-3 with an RO CF of 60.8%.